THE CONCEPT OF 'IHDAD HUSBAND WHO LIVED WITH THEIR WIFE (ANALYTICAL STUDY OF QIRAAH MUBADALAH'S INTERPRETATION) - Syahriyati, Laili Izza (Nurani, 2020)
The purpose of the research is implementation of ihdad husband whose wife died. The interpretation of ihdad was assessed as gender biased because it only talks about women. Women whose husbands die have a period of iddah and ihdad. Al-Quran texts and hadith explain about some of the prohibitions of ihdad women. Classical Fiqh has nothing to say about ihdad for husbands. Next about ihdad husband will relation with Qiraah mubadalah. This research uses this type of research Yuridis-Normative. Qiraah mubadalah expalin about method of interpretation with in parallel subject text. That is Islamic texts that discuss the subject of women and men have the same meaning. the implementation of ihdad has a main goal is remember and respect and protect the feelings of the family who died. If hikmatuttasyri like that and then ihdad law not only apply to women, but applies also to men.